Faith Blocks Fiber: The Effect of Religiosity on Internet Adoption among Indonesia’s Digital Immigrants - Yanti, Mery (Jurnal Sosiologi Reflektif, 2025)
Indonesia has experienced a rapid increase in internet adoption over the past decade, including among older adults often labeled as digital immigrants. Despite this growth, limited research has explored how sociocultural factors, particularly religiosity, shape digital engagement among this demographic. This study investigates the extent to which religiosity affects internet adoption among digital immigrants in Indonesia, while controlling for welfare, happiness, education, gender, and employment status. Adopting a quantitative design, the research employs data from the fifth wave of the Indonesian Family Life Survey (IFLS 2014–2015), focusing on individuals aged 35 to 69. Core variables were operationalized using validated survey instruments and analyzed through binary logistic regression via STATA 15. The finding reveals a significant negative correlation between religiosity and internet use, indicating that higher levels of religious commitment may inhibit digital engagement. Conversely, education, welfare, and happiness exhibit positive associations, with formal education emerging as the most robust predictor. The implication of this finding is that digital inclusion initiatives must be attuned to cultural and religious contexts to promote equitable and meaningful access to digital technologies. Penggunaan internet di Indonesia meningkat pesat dalam satu dekade terakhir, termasuk di kalangan digital immigrant, yaitu orang dewasa yang mulai mengenal teknologi di usia lanjut. Meski jumlah pengguna dari kelompok usia ini terus bertambah, faktor-faktor sosial budaya yang memengaruhi keterlibatan mereka dalam dunia digital, khususnya aspek religiusitas masih jarang diteliti. Penelitian ini bertujuan untuk melihat sejauh mana religiusitas memengaruhi penggunaan internet di kalangan digital immigrants di Indonesia, dengan mempertimbangkan juga faktor kesejahteraan, kebahagiaan, pendidikan, jenis kelamin, dan status pekerjaan. Penelitian ini menggunakan pendekatan kuantitatif dengan data dari Indonesian Family Life Survey (IFLS) tahun 2014–2015, yang mencakup responden berusia 35 hingga 69 tahun. Variabel-variabel kunci dianalisis menggunakan regresi logistik biner dengan bantuan STATA 15. Hasil penelitian menunjukkan bahwa tingkat religiusitas yang tinggi berkaitan dengan kemungkinan lebih rendah untuk menggunakan internet. Sebaliknya, pendidikan, kesejahteraan, dan kebahagiaan berhubungan positif dengan penggunaan internet, dengan pendidikan menjadi faktor paling kuat. Implikasi dari temuan ini adalah bahwa strategi perluasan akses digital sebaiknya mempertimbangkan nilai-nilai budaya dan agama sehingga dapat mendorong pemanfaatan teknologi yang lebih inklusif dan diterima masyarakat.